Distribuição espacial da agropecuária no Estado do Paraná : um estudo da função de produção - Pinheiro, Maria Andrade (2007)
The main propose of this work is study the agriculture production function of Paraná (Brazil) for the year 2002, contemplating its 399 cities and using spatial econometrics techniques. The use of this technique is intended to verify the behavior of many spatial elements such as the spatial dependence and the spatial heterogeneity. At a first moment it was used the exploratoty spatial data analysis (ESDA) showed that spatial dependence between the cities of the State considering the grow value of the agriculture production. The results had demonstrated that spatial dependence between the cities exists and that the biggest gross values are found in the situated cities in the North and West in the regions of the State. By means of the great maps of clusters it was verified existence of two clusters of type AA and three of type BB. The first one of type AA is situated in the Southwestern/West of the State and the other in North of the Paraná. Clusters of type BB is placed in the Northwest, Center and East of the Paraná. The estimate of production function using the classic model. The model production function that was better adjusted estimate for the spatial dependence in regression error terms - the not model elements determine the dependence between the cities. After the verification of the spatial dependence, studied the behavior of the spatial heterogeneity that is as the element studied for this methodology, having as purpose to measure the structural instability in the considered variable. After to divide the cities of the State in four regions measures a model considering this division and the joined result indicated that the function of production of the agriculture of the state does not follow the same structure in the cities. The locality of the cities intervenes in such a way, in its agriculture and each region can intervene with the production of its neighbor. It was proven supremacy of the West and North of the State in the farming production and low the participation of the Region Metropolitan of Curitiba in this segment. Each region was concluded thus, that politics of regional development must after be implemented detailed studies of each locality, therefore has proper characteristics. The risks not to adopt this type of behavior can generate resulted different in the diverse regions, low result of the implemented program and wastefulness of public mount of money.